The hidden costs of drug and alcohol use in hospital emergency departments. (21st July 2015) - Butler, Kerryn; Reeve, Rebecca; Arora, Sheena; Viney, Rosalie; Goodall, Stephen; van Gool, Kees; Burns, Lucinda
Abstract: Introduction and Aims: This study estimates the burden of drug and alcohol morbidity on hospitals in New South Wales (NSW) by observing a multi‐site collective sample utilising survey information and data linkage. Specifically we aimed to determine the prevalence of alcohol and other drug (AOD) problems and to estimate patterns of utilisation of hospital services, costs of presentations, and admissions for patients with AOD problems. Design and Methods: Patients were recruited from eight NSW public hospitals presenting to the hospital emergency department over a 10 day period. Participants completed a self‐administered survey with demographic characteristics and questions about substance use. More than two‐thirds (68%) of participants consented to provide access to their NSW Health medical data for a period spanning 2.5 years. Results: One‐third (35%) of the total sample were identified as having problematic AOD use with one in five of these patients requiring a high level of intervention. Those patients requiring a high level of intervention present more often and cost more per presentation. If admitted they were more likely to have longer stays and were also more likely to be admitted to a psychiatric ward and have a longer stay in the ward. Discussion: This study demonstrates a need for AOD interventions in the emergency department setting, both because it represents an opportunity for intervention in a population in which problems with substance use is highly prevalent, and because there is evidence that AOD imposes additional costs on the health system. [Butler K, Reeve R, Arora S, Viney R, Goodall S, van Gool K, Burns L. The hidden costs of drug and alcohol use in hospital emergency departments . Drug Alcohol Rev 2016;35:359–366]